Post-myocardial transitional care in Poland - single centre experience with novel Coordinated Comprehensive Care programme – clinical and laboratory follow-up. (25th November 2020) - Telec, W; Krysztofiak, H; Kalmucki, P; Baszko, A; Szyszka, A
Abstract: Background: Cardiac rehabilitation (CR) is an inherent part of the transitional care after acute myocardial infarction (AMI). Polish health care system has created a novel Coordinated Comprehensive Care Program after AMI, which ensures outpatient follow-ups, further invasive treatment and free-of-charge CR for all patients after acute MI. Purpose: The aim of the study was to analyze the impact of CR on clinical and laboratory characteristics of the patients who completed the recommended programme. Methods: 118 participants were enrolled. They were divided into two groups, depending on the criterium of completion (rehabilitation group) or non-completion (no rehabilitation group) of the CR. The clinical and laboratory data at discharge and after 12 months were collected and analyzed in both groups. Results: The majority of the patients (n=83, 70, 3%) underwent CR. This group was younger in comparison to patients who did not participate in CR (63.0±8.6 vs. 69.8±8.7 years; p<0.01). Index hospitalization was significantly shorter in rehabilitation group (7 vs. 8 days, respectively; p<0, 04). LDL-C reduction was observed in both groups, but only rehabilitation group presented statistically significant reduction (median LDL at discharge 108, 5 vs. 67, 0 mg/dl at follow-up; p<0.01). No rehabilitation group had LDL-C non-significantly decreased (p=0.16). NT-proBNP decreased in both groups over 12 months, but only rehabilitation group had significant reduction (median 590, 0 pg/ml at discharge vs. 199, 0 at follow-up; p<0.01). Laboratory follow-up is summarized in Figure 1. BMI increased in both groups, with statistical importance in rehabilitation group (p<0, 01). Conclusions: Post-myocardial rehabilitation is more frequently prescribed to younger patients with shorter index hospitalisation. Clinical and laboratory parameters improve more in the group that underwent CR programme and this might warant more effort on increasing CR accessibility and patient enrollement. The phenomenon of weight gain in patients after acute myocardial infarction independently from undergoing rehabilitation program or not needs further research. Funding Acknowledgement: Type of funding source: None